Kajian Faktor Fisik Lingkungan Kerja Yang Berhubungan Dengan Tingkat Kelelahan Pada Tenaga Kerja Di Unit Spinning IV PT. Sinar Pantja Djaja Semarang - Suliswati, Lilik; Setiani, Onny; Joko, Tri (Jurnal Kesehatan Lingkungan Indonesia, 2007)
ABSTRACT : Background : Production process in a textile industry may cause adverse effect on health of workes. One adverse effect is   from machines and working  environment that may produce noise   and hot environment that can give negative impact on worker. Noise  and heat excess  in working  environment can cause  fatigue and decrease  productivity of worker. The research aim was to find out the physical environmental factor that cause fatigue on worker in unit of spinning IV PT. Sinar Pantja Djaja Semarang. Method : This research was an observational study with a cross sectional approach. Sample taken for  this research were 45 worker. Data was taken by the measurement of noise intensity  and ambient temperature in production room, fatigue measurement was taken with reaction timer.  Data were  analized by using pearson product moment correlation and multiple regression  analysis. Result : This research showed that noise intensity average   was measured  91.70 dB and   average of ambient temperature  was about   30.650C. Time reaction  average to   light stimulus before working was 218,48 millisecond, time average reaction to light stimulus after working was measured 412,78 millisecon.d. Result of statistical test showed that  there was a  significant correlation between noise intensity and fatigue level  (p-0.005), ambient  temperature and fatigue  level (p-0.1222). The result of multiple linear Regression showed that noise intensity has correlation with fatigue. Conclusion To decrease the impact of noise on worker, workers need to wear hearing protective devices and  take a rest outside the production room. It is suggested that silencer is needed to decrease noise intensity  and a appropriate ventilation and exhaust fan must be installed to meet the standard of   working area for industry. Drinking water with mineral suplementation must be added to the management program to decrease the impact of heat stress on workers.   Keyword    : noise intensity, ambient temperature, heat, time reaction , and  fatigue level.